Decolonising Indigenous education: the case for cultural mentoring in supporting Indigenous knowledge reproduction. Issue 1 (2nd January 2022) - Burgess, Catherine; Bishop, Michelle; Lowe, Kevin
ABSTRACT: Little research exists about Indigenous-led teacher professional learning to improve skills in developing culturally responsive practices in schooling. This paper addresses a noticeable gap in the literature, that of Indigenous people mentoring non-Indigenous teachers to develop culturally responsive pedagogies. In the Australian context, the Decolonising Race Theory framework analyses the impact of an Aboriginal cultural mentoring programme for teachers, shifting the narrative away from racialised discourses about Aboriginal peoples to acknowledging Aboriginal educators as sovereign peoples. Key findings reveal that teachers' growing understanding of the ongoing impact of colonisation on Aboriginal families resulted in increased confidence in building relationships with Aboriginal communities, Country and students and implementing culturally responsive curriculum and pedagogies. The DRT analysis also raises serious questions about systemic challenges to be addressed if Aboriginal student outcomes are to improve.